2017
DOI: 10.24874/ti.2017.39.03.15
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive Wear Resistance, Mechanical Behaviour, Water Transport Phenomena and Biocorrosion of Epoxy/Femora Biocomposites

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The results obtained may be related to the MS microstructure. 34,43 Indeed, the MS microstructure makes the matrix-filler blend stiffer and relatively harder than pure UHMWPE. Subsequently, the increase in the hardness of the composite leads to a decrease in its ductility and thus its deformation at failure.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained may be related to the MS microstructure. 34,43 Indeed, the MS microstructure makes the matrix-filler blend stiffer and relatively harder than pure UHMWPE. Subsequently, the increase in the hardness of the composite leads to a decrease in its ductility and thus its deformation at failure.…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed an improvement in the wear performance of reinforced epoxy composites (minimal wear for composites filled with 6 wt % of waste), with the wear resistance properties being further improved with the addition of glass microspheres. The abrasive wear resistance of bovine femora-reinforced epoxy composites with 0–20 wt % of filler was determined by Olajide et al [ 16 ]. The authors indicated that the 20 wt % of waste significantly improved the antiwear properties of the composite.…”
Section: Agricultural Waste Materialsmentioning
confidence: 99%
“…The above results refer to the nature of the microstructure of MS. [ 29, 30 ] The MS microstructure makes the mixture of polymer and MS stiffer and relatively harder than pure UHMWPE. In addition, UHMWPE is a semi crystalline thermoplastic where, in the presence of MS particles, it loses its stretchability.…”
Section: Mechanical Behavior Of Mollusk Shell‐uhmwpe Biocompositementioning
confidence: 99%